2016
DOI: 10.1371/journal.pone.0160732
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tumor Response after Short-Course Radiotherapy and Delayed Surgery for Rectal Cancer

Abstract: PurposeNeoadjuvant therapy is able to reduce local recurrence in rectal cancer. Immediate surgery after short course radiotherapy allows only for minimal downstaging. We investigated the effect of delayed surgery after short-course radiotherapy at different time intervals before surgery, in patients affected by rectal cancer.MethodsFrom January 2003 to December 2013 sixty-seven patients with the following characteristics have been selected: clinical (c) stage T3N0 ≤ 12 cm from the anal verge and with circumfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…So, the question is why short-course chemoradiation has produced such a good result. There are several reasons that could explain the more favorable results in this study; firstly, the precise delineation of target volumes based on international guidelines [14] and the strict confirmation of treatment plans, considering the sufficient coverage of PTV and also the dose of organs-at-risk; second, administration of capecitabine with radiotherapy instead of bolus 5FU is shown to be associated with fewer toxicities and higher response rates in a study by Haddad et al [30]; third, prolonging the interval between radiotherapy completion and surgery to more than 8 weeks, as this has been demonstrated by Rega et al [31] to reduce adverse events and increase response to neoadjuvant therapy. In our study, the interval from end of radiotherapy to surgery was higher compared with the majority of other similar studies.…”
Section: Discussionmentioning
confidence: 94%
“…So, the question is why short-course chemoradiation has produced such a good result. There are several reasons that could explain the more favorable results in this study; firstly, the precise delineation of target volumes based on international guidelines [14] and the strict confirmation of treatment plans, considering the sufficient coverage of PTV and also the dose of organs-at-risk; second, administration of capecitabine with radiotherapy instead of bolus 5FU is shown to be associated with fewer toxicities and higher response rates in a study by Haddad et al [30]; third, prolonging the interval between radiotherapy completion and surgery to more than 8 weeks, as this has been demonstrated by Rega et al [31] to reduce adverse events and increase response to neoadjuvant therapy. In our study, the interval from end of radiotherapy to surgery was higher compared with the majority of other similar studies.…”
Section: Discussionmentioning
confidence: 94%
“…173 However, a higher grade of tumour regression, and even pCR, can be acheived if surgery is delayed at least 4 weeks after SRT. 149,[174][175][176] CRT induces more pCR than SRT, mainly because of the timing of surgery. 142,177 Another, registry based, study found that SRT-delay was less likely to induce pCR compared to CRT, adjusted OR (95% CI) 0.3 (0.2-0.5).…”
Section: Tumour Regressionmentioning
confidence: 99%
“…2,4 However, in some centers, apart from treatment with 5 × 5 Gy with a short (5-7 days) break, also 5 × 5 Gy and a long (4-5 weeks) break schedule before surgery is applied, and both were used in our study. Some authors 1,[5][6][7] suggest that SCRT with delayed surgery is suitable for early cancer.…”
Section: Introductionmentioning
confidence: 99%